The Efforts to Warn Corruption Through Education an Idiological Approach in Order Meet The Right to Country Rights - Adi Mansar (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
Education is placed in a strategic position to ensure the sustainability of a nation and state, therefore every effort or act that damages the integrity of the state must be fought massively. Forms of actions that are destructive and can threaten the integrity of the nation such as Terrorism, Narcotics and Psychotropic, Corruption and Trafficking in Persons. The integrity of the nation and state can be threatened due to systematic and massive and systematic structured corruption that has taken place from high-ranking officials to the village officials, proven that many cabinet ministers in power become suspects / defendants (i.c. Idrus Marham) Minister of Social Affairs RI Working Cabinet, Governor, Regents and Mayors, Civil Servants, Village Heads and also Senate and Legislative members ranging from Central to District. In the effort to implement corruption prevention and eradication as mandated in Presidential Regulation Number 55 of 2012 concerning National Strategy for the Prevention and Eradication of Long-Term Corruption in 2012-2025 and the Medium-Term 2012-2014 (National Strategy for CPE), and as an implementation, the preparation of Prevention and Eradication actions is carried out. Corruption (PPK) every year which is subsequently issued by Presidential Instruction Number 2 of 2014 concerning Action to Prevent and Eradicate Corruption in 2014, where in the attachment of the Presidential Instruction to part V (five) is explained about education strategies and anti-corruption culture consisting of 22 action plan, and including involving public and private higher education institutions in their implementation.